Organic film forming material, substrate, organic film forming method, pattern forming method, and organic film forming compound

By using organic film formation compounds with screw structure or cadole structure in semiconductor device manufacturing, combined with high boiling point solvents and other additives, the problems of substrate corrosion and insufficient film characteristics under high temperature conditions are solved, and high heat resistance and The organic film formation with planarization characteristics improves manufacturing yield and etch selectivity.

CN114942568BActive Publication Date: 2025-01-17SHIN ETSU CHEMICAL CO LTD
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
CN202210135076.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-02-15
Filing Date
2022-02-14
Publication Date
2025-01-17
Estimated Expiration
2042-02-14

AI Technical Summary

Technical Problem

In the manufacturing of existing semiconductor devices, the organic film materials used are prone to corrosion of the substrate under high temperature conditions, affecting productivity, and it is difficult to form a film with high heat resistance, adhesion and planarization characteristics, resulting in etch selectivity and yield. question.

Method used

Using a material containing a specific organic film forming compound, which has a spiral structure or a cadole structure, adjusts the molecular weight ratio by gel permeation chromatography, and combines a high boiling point solvent and an acid generator, a surfactant, and a crosslinking agent. and plasticizer, an organic film capable of hardening in a passive gas is formed.

Benefits of technology

It is achieved that hardening does not produce by-products under high temperature conditions, forming an organic film with high heat resistance and good landfill/planarization characteristics, and improving the manufacturing yield and etching resistance of semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114942568B_ABST
    Figure CN114942568B_ABST
Patent Text Reader

Abstract

The present invention relates to a material for forming an organic film, a substrate, a method for forming an organic film, a method for forming a pattern, and a compound for forming an organic film. The subject and object of the present invention are to provide a compound having a dioxin structure that can be hardened even under film-forming conditions in an inert gas, can form an organic underlayer film with excellent heat resistance, filling or planarization characteristics of a pattern formed on a substrate, and good film-forming properties and adhesion to the substrate, and a material for forming an organic film containing the compound. The solution of the present invention is a material for forming an organic film, characterized by containing: (A) a compound for forming an organic film represented by the following general formula (1A), and (B) an organic solvent. [Chemical formula 1] #imgabs0# In the formula, W1 is a tetravalent or hexavalent organic group, n1 represents an integer of 1 or 2, n2 represents 2 or 3, and R1 each independently represents any one of the following formula (1B); in addition, the hydrogen atoms of the benzene ring in the formula may also be substituted with fluorine atoms. [Chemical formula 2] #imgabs1#
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an organic film forming material used in a semiconductor device manufacturing step, a semiconductor device manufacturing substrate using the material, an organic film forming method, a pattern forming method using a multilayer resist method, and an organic film forming compound suitable for use with the above-mentioned material. Prior art

[0002] In the past, the high integration and high speed of semiconductor devices were achieved by miniaturizing the pattern size by shortening the wavelength of the light source in the photolithography technology (optical lithography) using light exposure as a general technology. In order to form such a fine circuit pattern on the semiconductor device substrate (processed substrate), a method of processing the processed substrate by dry etching using a photoresist film formed with a pattern as an etching mask is usually used. However, in reality, there is no dry etching method that can obtain complete etching selectivity between the photoresist film and the processed substrate, so in recent years, substrate processing by a multilayer resist method has been widely used. This method is to insert a lower film with different etching selectivity from the photoresist film (hereinafter referred to as the upper resist film) between the upper resist film and the processed substrate, and after the upper resist film obtains a pattern, the upper resist film pattern is used as a dry etching mask, and the pattern is transferred to the lower film by dry etching, and then the lower film is used as a dry etching mask, and the pattern is transferred to the processed substrate by dry etching.

[0003] One of the multilayer resist methods is a three-layer resist method that can be implemented using a general resist composition used in a single-layer resist method. This method is to form an organic lower film (hereinafter referred to as an organic film) by coating and calcining an organic lower film material composed of a composition containing an organic resin on a substrate to be processed, and then to form a silicon-containing film (hereinafter referred to as a silicon-containing resist intermediate film) by coating and calcining a resist intermediate film material composed of a composition containing a silicon-containing resin, and then to form a general organic photoresist film (hereinafter referred to as a resist upper film) thereon. If the resist upper film is patterned and then dry-etched using a fluorine-based gas plasma, the organic resist upper film can obtain a good etching selectivity ratio relative to the silicon-containing resist intermediate film, so the resist upper film pattern can be transferred to the silicon-containing resist intermediate film. According to this method, even if a resist upper layer film that does not have a sufficient film thickness for directly processing a substrate to be processed or a resist upper layer film that does not have sufficient dry etching resistance for processing a substrate to be processed is used, the pattern can still be easily transferred to the silicon-containing resist intermediate film because the film thickness of the silicon-containing resist intermediate film is usually equal to or less than that of the resist upper layer film. Then, the silicon-containing resist intermediate film to which the pattern is transferred is used as a dry etching mask, and the pattern is transferred to the organic film by dry etching using oxygen-based or hydrogen-based gas plasma, so that the pattern can be transferred to the organic film that has sufficient dry etching resistance for processing the substrate. The pattern of the organic film to which the pattern is transferred can be transferred to the substrate by dry etching using fluorine-based gas or chlorine-based gas.

[0004] On the other hand, the miniaturization in the manufacturing steps of semiconductor devices is gradually approaching the essential limit of the wavelength of the light source for optical lithography. Therefore, in recent years, there has been a study on the high integration of semiconductor devices that do not rely on miniaturization. As for one of the methods, there is a study on semiconductor devices with complex structures such as multi-gate structures, and some of them have been put into practical use. When forming such a structure by a multilayer resist method, an organic film material that can fill the holes, grooves, fins and other tiny patterns formed on the processed substrate with a film without leaving gaps, or can fill the height difference, or the pattern-dense part and the pattern-free area with a film and flatten (planarization) can be used. By using such an organic film material to form a flat organic film surface on a substrate with a height difference, the film thickness variation of the silicon-containing resist intermediate film and the resist upper film formed thereon can be suppressed, and the focus tolerance of optical lithography or the reduction of tolerance in the subsequent processing steps of the processed substrate can be suppressed. Thereby, semiconductor devices can be manufactured with good yield. On the other hand, in the single-layer photoresist method, in order to fill the processed substrate with height differences or patterns, the thickness of the upper resist film will become thicker, which will cause the pattern to collapse after exposure and development, or the pattern shape to deteriorate due to reflection from the substrate during exposure. The pattern formation tolerance during exposure becomes narrower, making it difficult to manufacture semiconductor devices with good yield.

[0005] In addition, as for the method of increasing the speed of the next generation semiconductor devices, the use of novel materials with high electron mobility such as strained silicon or gallium arsenic, or precision materials such as ultra-thin film polysilicon controlled in angstroms, has also begun to be explored. However, in the substrate to be processed using such novel precision materials, when the flattening film is formed using the organic film material as described above, for example, in the film forming conditions in the air at a temperature of 300°C or above, there is a possibility that the material of the processed substrate will be corroded by oxygen in the air, the performance of the semiconductor device cannot be achieved as designed, and the yield that can be realized in industrial production cannot be achieved. Therefore, in order to avoid the reduction in yield caused by the corrosion of the substrate caused by air under such high temperature conditions, an organic film material that can be formed in a passive gas is desired.

[0006] In the past, it is known that condensation resins obtained by using carbonyl compounds such as ketones or aldehydes and aromatic alcohols as condensing agents for phenolic and naphthol compounds are used as materials for forming organic films for multilayer resist methods. For example, fluorene bisphenol novolac resins described in Patent Document 1, bisphenol compounds and novolac resins thereof described in Patent Document 2, novolac resins of adamantane phenol compounds described in Patent Document 3, and bisnaphthol compounds and novolac resins thereof described in Patent Document 4 can be exemplified. Such materials are formed into films having solvent resistance to the coating film material used in the next step by crosslinking with a methylol compound as a crosslinking agent or by hardening due to crosslinking reaction caused by oxidation of aromatic rings at the α position by the action of oxygen in the air and subsequent condensation.

[0007] In addition, organic film materials that use triple bonds as intermolecular crosslinking groups of curable resins are known. For example, patent documents 5 to 15 are known. These materials form a cured film with solvent resistance not only through crosslinking from the above-mentioned methylol groups, but also through crosslinking by triple bonds. However, although these organic film-forming materials have excellent heat resistance, their properties such as flatness and adhesion to substrates are not sufficient and there is still room for improvement.

[0008] [Prior Technical Literature]

[0009] [Patent Document]

[0010] [Patent Document 1] Japanese Patent Application Publication No. 2005-128509

[0011] [Patent Document 2] Japanese Patent Application Publication No. 2006-293298

[0012] [Patent Document 3] Japanese Patent Application Publication No. 2006-285095

[0013] [Patent Document 4] Japanese Patent Application Publication No. 2010-122656

[0014] [Patent Document 5] Japanese Patent Publication No. 11-512430

[0015] [Patent Document 6] Japanese Patent Application Publication No. 2005-41938

[0016] [Patent Document 7] Japanese Patent Application Publication No. 2009-206447

[0017] [Patent Document 8] Japanese Patent Application Publication No. 2010-181605

[0018] [Patent Document 9] Japanese Patent Application Publication No. 2012-215842

[0019] [Patent Document 10] WO2014-208324

[0020] [Patent Document 11] Japanese Patent Application Publication No. 2016-44272

[0021] [Patent Document 12] Japanese Patent Application Publication No. 2016-60886

[0022] [Patent Document 13] Japanese Patent Application Publication No. 2017-14193

[0023] [Patent Document 14] Japanese Patent Application Publication No. 2017-119671

[0024] [Patent Document 15] Japanese Patent Application Publication No. 2018-92170 Summary of the invention

[0025] [Problems to be solved by the invention]

[0026] The present invention is made in view of the above facts, and aims to provide a compound that can be cured under film forming conditions not only in air but also in an inert gas, and can form an organic film having excellent heat resistance, excellent filling or flattening properties of a pattern formed on a substrate, and excellent film forming properties and adhesion to the substrate, and an organic film forming material containing the compound. In addition, the present invention also provides a semiconductor device manufacturing substrate, an organic film forming method, and a pattern forming method using the material.

[0027] [Methods to solve the problem]

[0028] In order to solve the above-mentioned problems, the present invention provides an organic film-forming material, comprising (A) an organic film-forming compound represented by the following general formula (1A), and (B) an organic solvent;

[0029] [Chemistry 1]

[0030]

[0031] (wherein W1 is a 4- or 6-valent organic group, n1 represents an integer of 1 or 2, n2 represents 2 or 3, and R1 each independently represents any one of the following formula (1B); in addition, the hydrogen atoms of the benzene ring in the formula may be substituted by fluorine atoms)

[0032] [Chemistry 2]

[0033]

[0034] Such an organic film forming material can harden under film forming conditions not only in air but also in an inert gas, and can form an organic film having high heat resistance, good adhesion to the substrate, and high filling / planarization properties.

[0035] Furthermore, the component (A) is preferably a compound represented by the following general formula (1C), (1D) or (1E).

[0036] [Chemistry 3]

[0037]

[0038] [Chemistry 4]

[0039]

[0040] [Chemistry 5]

[0041]

[0042] (In the above formula, n1 and R1 are the same as above.)

[0043] By introducing a spiro structure or cardo structure as described above into the organic film-forming compound, bending is introduced into the main skeleton, thereby relaxing the interaction between molecules and hindering crystallinity, thereby improving solubility in organic solvents and film-forming properties, and achieving the opposite performance of heat resistance and filling / planarization characteristics.

[0044] The component (A) is preferably a compound represented by the following formula (1F), (1G) or (1H).

[0045] [Chemistry 6]

[0046]

[0047] [Chemistry 7]

[0048]

[0049] [Chemistry 8]

[0050]

[0051] It is preferable from the viewpoint of heat resistance that the organic film-forming compound has a terminal structure as described above.

[0052] The ratio Mw / Mn of the weight average molecular weight Mw and the number average molecular weight Mn of the component (A) in terms of polystyrene obtained by gel permeation chromatography is preferably 1.00≤Mw / Mn≤1.10.

[0053] By controlling the Mw / Mn of the compound for forming an organic film within such a range, an organic film having excellent filling characteristics and flatness can be formed.

[0054] Furthermore, the component (B) is preferably a mixture of one or more organic solvents having a boiling point of less than 180 degrees and one or more organic solvents having a boiling point of 180 degrees or more.

[0055] Such an organic film-forming material can be provided with thermal fluidity by adding a high-boiling-point solvent to the organic film-forming compound, thereby achieving an organic film-forming material having both higher-level filling and planarizing properties.

[0056] The organic film-forming material preferably further includes one or more of (C) an acid generator, (D) a surfactant, (E) a crosslinking agent, and (F) a plasticizer.

[0057] The organic film-forming material of the present invention may contain one or more of the above-mentioned components (C) to (F) depending on the purpose.

[0058] In addition, the present invention provides a substrate for manufacturing a semiconductor device, on which an organic film obtained by curing the above-mentioned organic film-forming material is formed.

[0059] The organic film forming material of the present invention has both high filling and planarizing properties, thereby forming an organic film without microscopic voids due to poor filling or uneven surfaces of the organic film due to insufficient planarization. The substrate for semiconductor device manufacturing planarized with the organic film forming material of the present invention has a wide process latitude range during patterning, and semiconductor devices can be manufactured with good yield.

[0060] In addition, the present invention provides a method for forming an organic film, which is a method for forming an organic film used in the manufacturing steps of a semiconductor device, wherein the above-mentioned organic film forming material is spin-coated on a substrate to be processed, and the substrate to be processed coated with the organic film forming material is heat-treated at a temperature of 50° C. to 600° C. in a range of 10 seconds to 7200 seconds in an inert gas environment to obtain a cured film.

[0061] In addition, the present invention provides a method for forming an organic film, which is a method for forming an organic film used in the manufacturing steps of a semiconductor device, wherein the above-mentioned organic film forming material is spin-coated on a substrate to be processed, and the substrate to be processed coated with the organic film forming material is heat-treated in air at a temperature of 50°C to 600°C for a period of 5 seconds to 600 seconds to form a coating film, and then heat-treated in an inert gas environment at a temperature of 200°C to 600°C for a period of 10 seconds to 7200 seconds to obtain a cured film.

[0062] The organic film formed by the organic film forming method of the present invention and used in the manufacturing process of a semiconductor device has high heat resistance and high filling / planarization characteristics. If used in the manufacturing process of a semiconductor device, the yield of the semiconductor device becomes good.

[0063] Furthermore, the oxygen concentration in the inert gas is preferably 1% or less.

[0064] The organic film-forming material of the present invention can be sufficiently cured without generating sublimates even when heated in such an inert gas atmosphere, and can form an organic film having excellent adhesion to a substrate.

[0065] In addition, as the above-mentioned substrate to be processed, it is preferable to use a substrate to be processed having a structure with a height of 30 nm or more or a height difference.

[0066] The method for forming an organic film of the present invention is particularly useful when forming a flat organic film on such a substrate to be processed.

[0067] In addition, the present invention provides a pattern forming method, using the above-mentioned organic film forming material to form an organic film on a processed substrate, using a silicon-containing resist intermediate film material to form a silicon-containing resist intermediate film on the organic film, using a photoresist composition to form a resist upper film on the silicon-containing resist intermediate film, forming a circuit pattern on the resist upper film, using the resist upper film with the pattern formed as a mask to transfer the pattern to the silicon-containing resist intermediate film by etching, using the silicon-containing resist intermediate film with the pattern transferred as a mask to transfer the pattern to the organic film by etching, and further using the organic film with the pattern transferred as a mask to transfer the pattern to the processed substrate by etching.

[0068] In addition, the present invention provides a pattern forming method, which uses the above-mentioned organic film forming material to form an organic film on a processed substrate, uses a silicon-containing resist intermediate film material to form a silicon-containing resist intermediate film on the organic film, forms an organic anti-reflective film on the silicon-containing resist intermediate film, uses a photoresist composition to form a resist upper film on the organic anti-reflective film to form a four-layer film structure, forms a circuit pattern on the resist upper film, uses the patterned resist upper film as a mask to transfer the pattern to the organic anti-reflective film and the silicon-containing resist intermediate film by etching, uses the silicon-containing resist intermediate film with the transferred pattern as a mask to transfer the pattern to the organic film by etching, and further uses the organic film with the transferred pattern as a mask to transfer the pattern to the processed substrate by etching.

[0069] In addition, the present invention provides a pattern forming method, using the above-mentioned organic film forming material to form an organic film on a processed substrate, forming an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the organic film, using a photoresist composition to form a resist upper film on the inorganic hard mask, forming a circuit pattern on the resist upper film, using the resist upper film with the pattern formed as a mask to transfer the pattern to the inorganic hard mask by etching, using the inorganic hard mask with the transferred pattern as a mask to transfer the pattern to the organic film by etching, and further using the organic film with the transferred pattern as a mask to transfer the pattern to the processed substrate by etching.

[0070] In addition, the present invention provides a pattern forming method, which uses the above-mentioned organic film forming material to form an organic film on a processed substrate, forms an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film on the organic film, forms an organic anti-reflective film on the inorganic hard mask, uses a photoresist composition to form a resist upper film on the organic anti-reflective film to form a four-layer film structure, forms a circuit pattern on the resist upper film, uses the patterned resist upper film as a mask to transfer the pattern to the organic anti-reflective film and the inorganic hard mask by etching, uses the inorganic hard mask with the transferred pattern as a mask to transfer the pattern to the organic film by etching, and further uses the organic film with the transferred pattern as a mask to transfer the pattern to the processed substrate by etching.

[0071] The organic film forming material of the present invention can be suitably used in various pattern forming methods such as a three-layer resist process using a silicon-containing resist intermediate film or an inorganic hard mask, and a four-layer resist process using an organic anti-reflection film in addition to these. In the manufacturing process of a semiconductor device, if a circuit pattern is formed by such a pattern forming method of the present invention, a semiconductor device can be manufactured with good yield.

[0072] In addition, the inorganic hard mask is preferably formed by a CVD method or an ALD method.

[0073] The pattern forming method of the present invention can form an inorganic hard mask in this way, for example.

[0074] In forming the circuit pattern, it is preferable to form the circuit pattern by photolithography using light with a wavelength of 10 nm to 300 nm, direct drawing using an electron beam, nanoimprinting, or a combination thereof.

[0075] In the formation of the above-mentioned circuit pattern, the circuit pattern is developed by alkali development or organic solvent.

[0076] The pattern forming method of the present invention can appropriately use such circuit pattern forming means and developing means.

[0077] In addition, as the above-mentioned processed substrate, it is preferable to use a semiconductor device substrate, or a semiconductor device substrate on which a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film are formed.

[0078] In addition, as the above-mentioned metal, it is preferable to use one containing silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof.

[0079] According to the pattern forming method of the present invention, the above-mentioned substrate to be processed can be processed to form a pattern.

[0080] Furthermore, the present invention provides an organic film-forming compound represented by the following general formula (1A).

[0081] [Chemistry 9]

[0082]

[0083] (wherein W1 is a 4- or 6-valent organic group, n1 represents an integer of 1 or 2, n2 represents 2 or 3, and R1 each independently represents any one of the following formula (1B); in addition, the hydrogen atoms of the benzene ring in the formula may be substituted by fluorine atoms)

[0084] [Chemistry 10]

[0085]

[0086] Such a compound can be hardened under film-forming conditions not only in air but also in a passive gas, and can form an organic film having high heat resistance and high filling / planarization properties, and can form an organic film with excellent adhesion to the substrate through the action of a dioxin structure of a heterocyclic ring containing oxygen.

[0087] The organic film-forming compound is preferably represented by the following general formula (1C), (1D) or (1E).

[0088] [Chemistry 11]

[0089]

[0090] [Chemistry 12]

[0091]

[0092] [Chemistry 13]

[0093]

[0094] (In the above formula, n1 and R1 are the same as above.)

[0095] Such a compound can be a compound for forming an organic film with excellent solvent solubility without impairing heat resistance and filling / planarization characteristics due to the action of the cardo structure or the spiro structure, and has excellent film-forming properties regardless of the shape of the substrate to be processed.

[0096] Furthermore, the organic film-forming compound is preferably represented by the following formula (1F), (1G) or (1H).

[0097] [Chemistry 14]

[0098]

[0099] [Chemistry 15]

[0100]

[0101] [Chemistry 16]

[0102]

[0103] Such a compound can be a compound for forming an organic film that can be cured without generating by-products under any calcination conditions in air or in an inert gas, thereby exhibiting excellent heat resistance.

[0104] [Effects of the Invention]

[0105] As described above, the organic film forming compound of the present invention becomes a useful compound for forming an organic film having high degree of filling and planarization characteristics, heat resistance, etching resistance, film forming property, and adhesion even in the film formation in the inactive gas to prevent the corrosion of the substrate, and will not produce byproducts and will harden. In addition, the organic film forming material containing the compound is a material for forming an organic film having excellent filling / planarization characteristics and various characteristics such as heat resistance, etching resistance, adhesion to the substrate, and film forming property. Therefore, for example, it is an organic film material in a multilayer resist method such as a two-layer resist method, a three-layer resist method using a silicon-containing resist intermediate film, and a four-layer resist method using a silicon-containing resist intermediate film and an organic anti-reflective film, or as a planarizing material for semiconductor device manufacturing. In addition, the organic film formed by the organic film forming material of the present invention has excellent heat resistance, and even in the case of forming a CVD hard mask on the organic film, there is no film thickness change caused by thermal decomposition, and it is suitable for pattern formation. BRIEF DESCRIPTION OF THE DRAWINGS

[0106] [ Figure 1 ]An illustration of the flattening characteristics of the present invention.

[0107] [ Figure 2 ](A) to (F) are explanatory diagrams of an example of a pattern forming method according to the three-layer resist method of the present invention.

[0108] [ Figure 3 ](G)~(I) Illustrations of the landfill characteristic evaluation method in the embodiments.

[0109] [ Figure 4 ](J), (K) Illustrations of the flattening characteristic evaluation method in the embodiment.

[0110] [ Figure 5 ] Illustration of the method for measuring adhesion in the embodiment. DETAILED DESCRIPTION

[0111] As mentioned above, it is necessary to develop: an organic film forming material which does not produce by-products even under film forming conditions in a passive gas for preventing corrosion of the substrate, for example, above 300°C, and which can form an organic film with excellent filling or planarization characteristics of a pattern formed on the substrate and good dry etching resistance during substrate processing, and which does not cause thickness variation of the organic film due to thermal decomposition even when a CVD hard mask is formed on the organic film, and an organic film forming compound which is useful in a pattern forming method using the material.

[0112] Usually, when forming an organic film, an organic film-forming compound is dissolved in an organic solvent to form a composition, which is applied to a substrate on which a structure or wiring of a semiconductor device is formed, and then calcined to form an organic film. Immediately after the composition is applied, a coating film is formed following the shape of the height difference structure on the substrate, but if the coating film is calcined, most of the organic solvent will evaporate during the period until hardening, and the organic film will be formed with the organic film-forming compound remaining on the substrate. The inventors of this case thought that if the organic film-forming compound remaining on the substrate at this time has sufficient thermal fluidity, the height difference shape just after application can be flattened by thermal flow, thereby forming a flat film.

[0113] The inventors of the present case have repeatedly conducted in-depth studies and found that if the organic film forming compound is represented by the above-mentioned general formula (1A), the substituent represented by R1 has the same thermal curing property as the conventional underlying film material not only in air but also in inert gas, and the partial structure connected by the dioxin ring imparts adhesion, thermal fluidity, and a high degree of filling / planarization characteristics, thereby becoming an organic film forming composition that can provide heat resistance and no variation in coating film thickness due to thermal decomposition even in the case of forming a CVD hard mask, thereby completing the present invention.

[0114] That is, the present invention is an organic film-forming material comprising (A) an organic film-forming compound represented by the following general formula (1A), and (B) an organic solvent.

[0115] [Chemistry 17]

[0116]

[0117] (wherein W1 is a 4- or 6-valent organic group, n1 represents an integer of 1 or 2, n2 represents 2 or 3, and R1 each independently represents any one of the following formula (1B); in addition, the hydrogen atoms of the benzene ring in the formula may be substituted by fluorine atoms)

[0118] [Chemistry 18]

[0119]

[0120] Hereinafter, the present invention will be described in detail, but the present invention is not limited thereto.

[0121] <Organic film-forming compound>

[0122] The organic film-forming compound of the present invention is an organic film-forming compound represented by the following general formula (1A).

[0123] [Chemistry 19]

[0124]

[0125] (wherein W1 is a 4- or 6-valent organic group, n1 represents an integer of 1 or 2, n2 represents 2 or 3, and R1 each independently represents any one of the following formula (1B); in addition, the hydrogen atoms of the benzene ring in the formula may be substituted by fluorine atoms)

[0126] [Chemistry 20]

[0127]

[0128] In the general formula (1A), W1 preferably has at least one aromatic ring, and the bonds to the two oxygen atoms represented by the dotted line are formed as substituents on the aromatic ring constituting W1. The two oxygen atoms are preferably bonded to W1 adjacent to each other on the aromatic ring to form a 1,4-dioxin ring.

[0129] The compound of the general formula (1A) has a heterocyclic structure, and thus has excellent heat resistance and adhesion. In addition, the substituent represented by R1 can impart hardenability in the atmosphere and in the presence of an inert gas. Therefore, when an inorganic hard mask is formed on an organic film using the compound of the present invention by a CVD method or an ALD method, defects caused by insufficient heat resistance of the organic film and film peeling caused by insufficient adhesion can be prevented.

[0130] W1 in the general formula (1A) may be, for example, the following, and these aromatic rings may have a substituent, and examples of the substituent include an alkyl group having 1 to 10 carbon atoms, an alkynyl group and an alkenyl group having 3 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, a nitro group, a halogen group, a nitrile group, an alkoxycarbonyl group having 1 to 10 carbon atoms, and an alkanoyloxy group having 1 to 10 carbon atoms. Among these, those having a fluorene or spiro structure are preferred from the viewpoint of heat resistance and flatness.

[0131] [Chemistry 21]

[0132]

[0133] The compound for forming an organic film of the present invention is preferably a compound having a structure represented by the following general formula (1C), (1D) or (1E).

[0134] [Chemistry 22]

[0135]

[0136] [Chemistry 23]

[0137]

[0138] [Chemistry 24]

[0139]

[0140] (In the above formula, n1 and R1 are the same as above.)

[0141] By introducing a fluorene structure or a spiro structure into the main skeleton represented by the general formulae (1C), (1D) and (1E), excellent solubility in organic solvents can be imparted, and the contradictory properties of heat resistance and filling / planarization properties can be combined.

[0142] The compound for forming an organic film of the present invention is preferably represented by the following formula (1F), (1G) or (1H).

[0143] [Chemistry 25]

[0144]

[0145] [Chemistry 26]

[0146]

[0147] [Chemistry 27]

[0148]

[0149] Due to the action of the acetylene groups introduced into the terminal structures of the above formulae (1F), (1G) and (1H), no by-products are generated when the organic film is baked for thermal curing, thereby suppressing thermal shrinkage of the film.

[0150] The organic film-forming compound of the present invention is preferably an organic film-forming compound having a ratio Mw / Mn of a polystyrene-equivalent weight average molecular weight Mw to a number average molecular weight Mn of 1.00≤Mw / Mn≤1.10 as determined by gel permeation chromatography.

[0151] By controlling the Mw / Mn of the compound for forming an organic film within such a range, an organic film having excellent filling characteristics and flatness can be formed.

[0152] When the Mw / Mn ratio is within the above range, the thermal fluidity of the organic film-forming compound becomes better. Therefore, when it is added to the composition, it can not only fill the fine structure formed on the substrate well, but also form an organic film with a flat substrate as a whole.

[0153] [Method for producing organic film-forming compound]

[0154] As for the means for obtaining the organic film forming compound of the present invention, it can be synthesized by using a base catalyst as shown below to carry out a substitution reaction between difluorobenzenes having a substituent R1 and tetrahydric alcohols or hexahydric alcohols. In this case, the tetrahydric alcohols or hexahydric alcohols are preferably compounds having 2 or 3 groups of adjacent phenolic hydroxyl groups on the aromatic ring as described above. In addition, the difluorobenzenes, tetrahydric alcohols, and hexahydric alcohols having a substituent R1 used in the synthesis can be used alone or in combination of two or more. These can be appropriately selected and combined according to the required characteristics. W1, R1, n1, and n2 in the following formula are as described above.

[0155] [Chemistry 28]

[0156]

[0157] As for the base catalyst used at this time, inorganic base compounds such as sodium bicarbonate, sodium carbonate, potassium carbonate, calcium carbonate, cesium carbonate, sodium hydroxide, potassium hydroxide, sodium hydride, potassium phosphate, triethylamine, pyridine, organic amine compounds such as N-methylmorpholine, etc. can be listed, and these can be used alone or in combination of two or more. The usage amount of these catalysts is preferably 0.1 to 20 moles, more preferably 0.2 to 10 moles relative to 1 mole of the hydroxyl group of the tetrahydric alcohol or hexahydric alcohol of the raw material.

[0158] As for the solvent used at this time, there is no particular limitation as long as it is a solvent inactive to the above reaction, for example, ether solvents such as diethyl ether, tetrahydrofuran, dioxane, aromatic solvents such as benzene, toluene, xylene, acetonitrile, dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, water, etc., which can be used alone or in combination. These solvents can be used in a range of 0 to 2000 parts by mass relative to 100 parts by mass of the reaction raw materials, and the reaction temperature is preferably about -50°C to the boiling point of the solvent, more preferably room temperature to 150°C. The reaction time is preferably appropriately selected from 0.1 to 100 hours.

[0159] As for the reaction method, there are methods of adding difluorobenzenes, tetrahydric alcohols or hexahydric alcohols together to a solvent, methods of adding difluorobenzenes and tetrahydric alcohols or hexahydric alcohols separately after dispersing or dissolving the latter, or mixing and dispersing or dissolving the latter, and then adding dropwise, and methods of adding after dispersing or dissolving any one of difluorobenzenes, tetrahydric alcohols or hexahydric alcohols in a solvent and then adding dropwise the other one dispersed or dissolved in the solvent, etc. In addition, when multiple types of difluorobenzenes, tetrahydric alcohols or hexahydric alcohols are added separately, they can be mixed in advance to react, or they can be reacted individually in sequence. When using an alkali catalyst, there can be cited methods of adding together with difluorobenzenes, tetrahydric alcohols or hexahydric alcohols, and methods of adding dropwise after dispersing or dissolving the alkali catalyst in advance, etc.

[0160] The obtained reaction solution can be diluted with an organic solvent for removing unreacted raw materials, catalysts, etc. present in the system, and then separated, washed, and recovered.

[0161] As for the organic solvent used in the liquid separation cleaning, there is no particular limitation as long as it is a soluble compound that separates into two layers when mixed with water. Examples include hydrocarbons such as hexane, heptane, benzene, toluene, and xylene, esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate, ketones such as methyl ethyl ketone, methyl amyl ketone, cyclohexanone, and methyl isobutyl ketone, ethers such as diethyl ether, diisopropyl ether, methyl-tert-butyl ether, and ethyl cyclopentyl methyl ether, chlorine-based solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene, and mixtures thereof. As for the cleaning water used at this time, deionized water or ultrapure water is generally used. The number of cleaning times may be more than one, but even if the cleaning is performed more than 10 times, the corresponding cleaning effect may not be obtained, and it is preferably about 1 to 5 times.

[0162] In order to remove unreacted raw materials or acidic components in the system during liquid separation and washing, washing with an alkaline aqueous solution can also be performed. As for the base, specific examples include alkali metal hydroxides, alkali metal carbonates, alkaline earth metal hydroxides, alkaline earth metal carbonates, ammonia, and organic ammonium.

[0163] In addition, in order to remove unreacted raw materials, metal impurities or alkaline components in the system during liquid separation and cleaning, cleaning can also be performed with an acidic aqueous solution. As for the acid, specific examples include inorganic acids such as hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and heteropoly acids, and organic acids such as oxalic acid, fumaric acid, maleic acid, trifluoroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid.

[0164] The liquid separation washing using the alkaline aqueous solution or the acidic aqueous solution may be performed alone or in combination. It is preferable to perform the liquid separation washing using the alkaline aqueous solution and the acidic aqueous solution in this order from the viewpoint of removing metal impurities.

[0165] After the above-mentioned separation cleaning using alkaline aqueous solution or acidic aqueous solution, it is also possible to clean with neutral water. As for neutral water, the deionized water or ultrapure water mentioned above can be used. The number of cleaning times is 1 or more, but if the number is less, the alkaline components and acidic components may not be removed. However, even if the cleaning is performed more than 10 times, the corresponding cleaning effect may not be obtained, so it is preferably about 1 to 5 times.

[0166] In addition, the reaction product after the liquid separation operation can also be recovered as a powder by concentrating and drying the solvent or crystallizing it under reduced pressure or normal pressure. In order to improve the operability when modulating the organic film forming material, it can also be made into a solution state of appropriate concentration. As for the concentration at this time, it is preferably 0.1 to 50% by mass, and more preferably 0.5 to 30% by mass. If it is such a concentration, it is not easy to become high viscosity and can prevent damage to operability. In addition, the amount of solvent will not become too much and is economically preferred.

[0167] The solvent in this case is not particularly limited as long as it can dissolve the compound. Specific examples include ketones such as cyclohexanone and methyl-2-pentyl ketone; alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, and 1-ethoxy-2-propanol; ethers such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, and diethylene glycol dimethyl ether; and esters such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, and propylene glycol monotert-butyl ether acetate. These may be used alone or in combination of two or more.

[0168] In the above reaction, difluorobenzenes, tetrahydric alcohols or hexahydric alcohols can be combined to match the desired performance. Specifically, those obtained by introducing substituents that impart solvent solubility, adhesion, hardening, filling / planarization characteristics, etching resistance, and film-forming properties in accordance with the desired performance can be used. Organic film materials using these compounds can have both filling / planarization characteristics and heat resistance at a high level.

[0169] As described above, the compound for forming an organic film of the present invention can provide an organic film-forming composition having both heat resistance at 400° C. or higher and high filling / planarization properties.

[0170] In the present invention, the planarization property is the property of planarizing the surface of a substrate. Figure 1 As shown, an organic film forming composition 3' is applied on a substrate 1 and heated to form an organic film 3, thereby reducing the height difference of 100nm in the substrate 1 to less than 30nm. Figure 1 The height difference shapes shown are typical examples of the height difference shapes in the substrate for manufacturing a semiconductor device, and the height difference shapes of the substrate that can be planarized by the composition containing the organic film-forming compound of the present invention are naturally not limited to these.

[0171] <Organic film forming material>

[0172] In addition, the present invention provides an organic film-forming material (organic film-forming composition), comprising (A) the organic film-forming compound of the present invention represented by the above-mentioned general formula (1A) and (B) an organic solvent. In addition, in the organic film-forming material of the present invention, the organic film-forming compound of the present invention can be used alone or in combination of two or more.

[0173] As for the organic solvent that can be used in the organic film forming material of the present invention, there is no particular limitation as long as it can dissolve the constituent components contained in the above-mentioned compound and other additives. Specifically, solvents having a boiling point of less than 180° C. such as the solvents described in paragraphs

[0091] to

[0092] of Japanese Patent Publication No. 2007-199653 can be used. Among them, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, 2-heptanone, cyclopentanone, cyclohexanone and a mixture of two or more of these are preferably used. The amount of the organic solvent blended is preferably 200 to 10,000 parts, more preferably 300 to 5,000 parts, relative to 100 parts of the above-mentioned compound (A).

[0174] Such an organic film forming material can be applied by spin coating, and because it contains the organic film forming compound of the present invention, it can be an organic film forming material having both heat resistance of 400° C. or higher and high filling / planarization properties.

[0175] In addition, in the organic film forming material of the present invention, as an organic solvent, a high boiling point solvent having a boiling point of 180°C or higher (a mixture of a solvent having a boiling point of less than 180°C and a solvent having a boiling point of 180°C or higher) may be added to the above-mentioned solvent having a boiling point of less than 180°C. As the high boiling point organic solvent, there are no particular restrictions as long as it can dissolve the organic film forming compound, and it may be a hydrocarbon, alcohol, ketone, ester, ether, chlorine-based solvent, etc. Specific examples include 1-octanol, 2-ethylhexanol, 1-nonanol, 1-decanol, 1-undecanol, ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, 2-ethyl-1,3-hexanediol, diethylene glycol, diol Propylene glycol, triethylene glycol, tripropylene glycol, glycerol, n-nonyl acetate, ethylene glycol monohexyl ether, ethylene glycol mono-2-ethylhexyl ether, ethylene glycol monophenyl ether, ethylene glycol monobenzyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol monoisobutyl ether, diethylene glycol monohexyl ether, diethylene glycol monophenyl ether, diethylene glycol monobenzyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol mono Methyl ether, triethylene glycol n-butyl ether, triethylene glycol butyl methyl ether, triethylene glycol diacetate, tetraethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol mono-n-butyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, triethylene glycol monomethyl ether acetate Acid glycerol, propylene glycol diacetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol methyl n-propyl ether, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butanediol diacetate, 1,6-hexanediol diacetate, triethylene glycol diacetate, γ-butyrolactone, dihexyl malonate, diethyl succinate, dipropyl succinate, dibutyl succinate, dihexyl succinate, dimethyl adipate, diethyl adipate, dibutyl adipate and the like can be used alone or in combination.

[0176] The boiling point of the high boiling point solvent can be appropriately selected in accordance with the temperature of the heat treatment of the organic film forming material. The boiling point of the added high boiling point solvent is preferably 180°C to 300°C, more preferably 200°C to 300°C. If such a boiling point is used, there is no concern that the solvent volatilizes too quickly during baking (heat treatment) due to a too low boiling point, so sufficient thermal fluidity can be obtained. In addition, if such a boiling point is used, there is no fact that the solvent remains in the film without volatilization after baking due to a high boiling point, so there is no concern that the film properties such as etching resistance are adversely affected.

[0177] In addition, when the high boiling point solvent is used, the amount of the high boiling point solvent blended is preferably 1 to 30 parts by mass relative to 100 parts by mass of the solvent having a boiling point of less than 180° C. If the blended amount is such, there is no concern that if the blended amount is too small, sufficient thermal fluidity cannot be imparted during baking, or if the blended amount is too large, the solvent remains in the film, causing deterioration of film properties such as etching resistance.

[0178] Such an organic film-forming material can be made into an organic film-forming material having both high filling and planarizing properties by adding a high-boiling-point solvent to the organic film-forming compound to impart thermal fluidity.

[0179] In the organic film forming material of the present invention, in order to further promote the curing reaction, (C) an acid generator may be added. The acid generator is a material that generates an acid by thermal decomposition or a material that generates an acid by light irradiation, and any of them may be added. Specifically, the materials described in paragraphs

[0061] to

[0085] of Japanese Patent Publication No. 2007-199653 may be added, but are not limited thereto.

[0180] The acid generators may be used alone or in combination of two or more. The amount of the acid generator added is preferably 0.05 to 50 parts, more preferably 0.1 to 10 parts, based on 100 parts of the compound.

[0181] In the organic film forming material of the present invention, in order to improve the coating property in spin coating, a surfactant (D) may be added. As the surfactant, for example, those described in

[0142] to

[0147] in Japanese Patent Publication No. 2009-269953 may be used. When the surfactant is added, the amount added is preferably 0.01 to 10 parts, more preferably 0.05 to 5 parts, relative to 100 parts of the above-mentioned compound.

[0182] In addition, in the organic film forming material of the present invention, in order to improve the hardening property and suppress the intermixing with the upper film, (E) crosslinking agent may also be added. As a crosslinking agent, there is no particular limitation, and crosslinking agents of various known systems can be widely used. For example, melamine crosslinking agents, glycoluril crosslinking agents, benzoguanamine crosslinking agents, urea crosslinking agents, β-hydroxyalkylamide crosslinking agents, isocyanurate crosslinking agents, aziridine crosslinking agents, oxazoline crosslinking agents, and epoxy crosslinking agents can be exemplified.

[0183] As for melamine-based crosslinking agents, hexamethoxymethylated melamine, hexabutoxymethylated melamine, their alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be specifically exemplified. As for glycoluril-based crosslinking agents, tetramethoxymethylated glycoluril, tetrabutoxymethylated glycoluril, their alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be specifically exemplified. As for benzoguanamine-based crosslinking agents, tetramethoxymethylated benzoguanamine, tetrabutoxymethylated benzoguanamine, their alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be specifically exemplified. As for urea-based crosslinking agents, dimethoxymethylated dimethoxyethylene urea, its alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be specifically exemplified. As for β-hydroxyalkylamide-based crosslinking agents, N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide can be specifically exemplified. Specific examples of isocyanurate crosslinking agents include triglycidyl isocyanurate and triallyl isocyanurate. Specific examples of aziridine crosslinking agents include 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane and 2,2-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate]. Specific examples of the oxazoline crosslinking agent include 2,2'-isopropylidenebis(4-benzyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-methylenebis-4,5-diphenyl-2-oxazoline, 2,2'-methylenebis-4-phenyl-2-oxazoline, 2,2'-methylenebis-4-tert-butyl-2-oxazoline, 2,2'-bis(2-oxazoline), 1,3-phenylenebis(2-oxazoline), 1,4-phenylenebis(2-oxazoline), and 2-isopropenyloxazoline copolymers. Specific examples of epoxy crosslinking agents include diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-butylene glycol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, poly(glycidyl methacrylate), trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether. The amount of the crosslinking agent added is preferably 1 to 100 parts, more preferably 5 to 50 parts, based on 100 parts of the above compounds.

[0184] In addition, in the organic film forming material of the present invention, in order to further improve the planarization / burying characteristics, a (F) plasticizer may be added. As the plasticizer, there is no particular limitation, and plasticizers of various known systems can be widely used. For example, low molecular weight compounds such as phthalates, adipic acid esters, phosphates, trimellitic acid esters, and citrates, polyethers, polyesters, and polymers such as polyacetal polymers described in Japanese Patent Application Laid-Open No. 2013-253227 can be exemplified. The amount of the plasticizer added is preferably 1 to 100 parts, more preferably 5 to 30 parts, relative to 100 parts of the above-mentioned compound.

[0185] In addition, in the organic film forming material of the present invention, as an additive for imparting a filling / planarizing property similar to a plasticizer, for example, a liquid additive having a polyethylene glycol or polypropylene glycol structure, or a thermally decomposable polymer having a weight reduction rate of 40% by mass or more between 30°C and 250°C and a weight average molecular weight of 300 to 200,000 is preferably used. The thermally decomposable polymer is preferably one containing a repeating unit having an acetal structure represented by the following general formula (DP1) or (DP1a). The amount of these liquid additives added is preferably 1 to 100 parts, more preferably 5 to 50 parts, relative to 100 parts of the above-mentioned compound.

[0186] [Chemistry 29]

[0187]

[0188] (In the formula, X1 is a hydrogen atom or a saturated or unsaturated monovalent organic group having 1 to 30 carbon atoms which may be substituted. Y1 is a saturated or unsaturated divalent organic group having 2 to 30 carbon atoms.)

[0189] [Chemistry 30]

[0190]

[0191] (Where X a Y is an alkyl group having 1 to 4 carbon atoms. a It is a saturated or unsaturated divalent hydrocarbon group having 4 to 10 carbon atoms, and may also have an ether bond. l represents the average number of repeating units, which is 3 to 500.

[0192] As described above, the organic film forming material of the present invention has heat resistance of 400°C or more and high-level filling / planarization characteristics. Therefore, the organic film forming material of the present invention is extremely useful as an organic film forming material for a multilayer resist method such as a two-layer resist method, a three-layer resist method using a silicon-containing resist intermediate film or an inorganic hard mask, and a four-layer resist method using a silicon-containing resist intermediate film or an inorganic hard mask and an organic antireflection film. In addition, the organic film forming material of the present invention has excellent filling / planarization characteristics and does not produce by-products even when forming a film in an inert gas, so it can also be suitably used as a planarization material in a semiconductor device manufacturing step other than the multilayer resist method.

[0193] <Substrate for semiconductor device manufacturing>

[0194] Furthermore, the present invention provides a substrate for manufacturing a semiconductor device, on which an organic film obtained by curing the above-mentioned organic film-forming material is formed.

[0195] If the organic film formed by the organic film forming material of the present invention has a high degree of filling / planarization characteristics, it becomes an organic film without tiny voids due to poor filling or unevenness on the organic film surface due to insufficient planarization. The substrate for manufacturing semiconductor devices that is planarized with such an organic film has a wider process tolerance range during patterning, and semiconductor devices can be manufactured with good yield.

[0196] <Method for Forming Organic Film>

[0197] The present invention provides a method for forming an organic film, which is a method for forming an organic film used in the manufacturing steps of a semiconductor device, wherein the above-mentioned organic film forming material is spin-coated on a substrate to be processed, and the above-mentioned substrate to be processed coated with the organic film forming material is heat-treated in an inert gas environment at a temperature of 50° C. to 600° C. for 10 seconds to 7200 seconds to obtain a cured film (first-stage baking).

[0198] In addition, the present invention provides a method for forming an organic film, which is a method for forming an organic film that can flatten the surface of a high-height substrate used in the manufacturing steps of a semiconductor device, wherein the organic film forming material of the present invention is spin-coated on a substrate to be processed, and the substrate to be processed coated with the organic film forming material is heat-treated in air at a temperature of 50°C to 300°C for 5 to 600 seconds to form a coating film, and then heat-treated in an inert gas environment at a temperature of 200°C to 600°C, preferably at a temperature of 250°C or more, for 10 to 7200 seconds to obtain a cured film (two-stage baking).

[0199] In the method for forming an organic film, first, the organic film forming material of the present invention is spin-coated (spin-coated) on the substrate to be processed. By using the spin coating method, good landfill characteristics can be obtained. After spin coating, baking (heat treatment) is performed to promote flattening and cross-linking reactions caused by heat flow. In addition, by this baking, the solvent in the organic film forming material can be evaporated, so when a resist upper film or a silicon-containing resist intermediate film is formed on the organic film, mixing can also be prevented.

[0200] The heating film-forming step for forming the organic film (organic lower layer film) can use single-stage baking, double-stage baking, or multi-stage baking of three or more stages. Single-stage baking or double-stage baking is more ideal in terms of economy.

[0201] The film formation by the one-step baking is performed in an inert gas environment at a temperature of 50° C. to 600° C. for 10 to 7200 seconds, preferably at a temperature of 150° C. to 500° C. for 10 to 3600 seconds. By performing the heat treatment under such conditions, planarization and crosslinking reactions due to thermal flow can be promoted.

[0202] In the multilayer resist method, a coating type silicon-containing resist intermediate film and a CVD hard mask are sometimes formed on the obtained film. When a coating type silicon-containing resist intermediate film is used, it is preferable to form the organic film at a temperature higher than the temperature at which the silicon-containing resist intermediate film is formed. Usually, the silicon-containing resist intermediate film is formed at a temperature of 100°C to 400°C, preferably 150°C to 350°C. If the organic film is formed at a temperature higher than this temperature, the dissolution of the organic film caused by the composition used to form the silicon-containing resist intermediate film can be prevented, and an organic film that does not mix with the composition can be formed. When a CVD hard mask is used, it is preferable to form the organic film at a temperature higher than the temperature at which the CVD hard mask is formed. As for the temperature at which the CVD hard mask is formed, a temperature of 150°C to 500°C can be exemplified.

[0203] On the other hand, in the film formation by two-stage baking, as the first stage baking, if the influence of corrosion of the substrate caused by oxygen in the air is considered, the processing temperature in the air is 50°C to 300°C, preferably 250°C or less, and it is carried out in the range of 5 to 600 seconds. The second stage baking is carried out in an inert gas, and as far as the baking temperature is concerned, it is higher than the baking temperature of the first stage, 200°C to 600°C, preferably 250°C to 500°C or less, and it is more ideal to carry out in the range of 10 to 7200 seconds.

[0204] In the multilayer resist method, a coating type silicon-containing resist intermediate film and a CVD hard mask are sometimes formed on the obtained film. When using a coating type silicon-containing resist intermediate film, it is preferable to form the organic film at a temperature higher than the temperature at which the silicon-containing resist intermediate film is formed. Usually, the silicon-containing resist intermediate film is formed at a temperature of 100°C to 400°C, preferably 150°C to 350°C. If the organic film is formed at a temperature higher than this temperature, the dissolution of the organic film caused by the composition used to form the silicon-containing resist intermediate film can be prevented, and an organic film that does not mix with the composition can be formed. In the case of using a CVD hard mask for two-stage baking, it is preferable to form the organic film at a temperature higher than the temperature at which the CVD hard mask is formed. As for the temperature for forming the CVD hard mask, a temperature of 150°C to 500°C can be exemplified.

[0205] In addition, the present invention provides an organic film forming method, which is an organic film forming method that functions as an organic underlayer film used in the manufacturing step of a semiconductor device. In order to prevent corrosion of the processed substrate, the processed substrate is heat treated in an environment with an oxygen concentration of less than 1% to form a hardened film.

[0206] In the organic film forming method, the organic film forming material of the present invention is first spin-coated (spin-coated) on the processed substrate. After spin-coating, two-stage baking is first carried out in air at a temperature below 300°C, and then the second-stage baking is carried out in an environment with an oxygen concentration of less than 1%. In the case of one-stage baking, the first-stage baking in air at the beginning can be skipped. In addition, as for the environment during baking, inert gases such as nitrogen, argon, and helium can be exemplified. As long as it is the organic film forming material of the present invention, even if it is calcined in such an inert gas environment, no sublimates will be produced and a fully hardened organic film can be formed.

[0207] In addition, the method for forming an organic film of the present invention can use a substrate to be processed that has a structure or a height difference of 30 nm or more. As described above, the material for forming an organic film of the present invention has excellent filling / flattening properties, so even if the substrate to be processed has a structure or a height difference (concave and convex) of 30 nm or more, a flat hardened film can be formed. That is, the method for forming an organic film of the present invention is particularly useful in the case of forming a flat organic film on such a substrate to be processed.

[0208] The thickness of the organic film to be formed can be appropriately selected, and is preferably 30 to 20,000 nm, and particularly preferably 50 to 15,000 nm.

[0209] Furthermore, the above-mentioned method for forming an organic film can be applied to both the case of forming an organic film for an organic underlayer film and the case of forming an organic film for a planarizing film using the organic film-forming material of the present invention.

[0210] <Pattern Formation Method>

[0211] [Three-layer resist method using a silicon-containing resist interlayer]

[0212] The present invention provides a pattern forming method, which comprises forming an organic film on a processed substrate using the organic film forming material of the present invention, forming a silicon-containing resist intermediate film on the organic film using a silicon-containing resist intermediate film material containing silicon atoms, forming a resist upper film on the silicon-containing resist intermediate film using a resist upper film material composed of a photoresist composition, forming a circuit pattern on the resist upper film, transferring the pattern to the silicon-containing resist intermediate film by etching using the resist upper film on which the circuit pattern is formed as a mask, transferring the pattern to the organic film by etching using the silicon-containing resist intermediate film on which the pattern is transferred, and further transferring the pattern to the processed substrate by etching using the organic film on which the pattern is transferred as a mask.

[0213] As the processed substrate, it is preferable to use a semiconductor device substrate, or a substrate obtained by forming a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film on the semiconductor device substrate. More specifically, there is no particular limitation, and a substrate of Si, α-Si, p-Si, SiO2, SiN, SiON, W, TiN, Al, etc. can be used, or a substrate obtained by forming the above-mentioned metal films as a processed layer on the substrate, etc.

[0214] As for the processed layer, various Low-k films such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, Al-Si and their barrier films can be used, and the thickness can be generally 50 to 10,000 nm, especially 100 to 5,000 nm. In addition, when forming the processed layer, the substrate and the processed layer are made of different materials.

[0215] In addition, as the metal on the processed substrate, it is preferable to use one containing silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or alloys thereof.

[0216] Furthermore, as the substrate to be processed, it is preferable to use a substrate to be processed having a structure with a height of 30 nm or more or a height difference.

[0217] When an organic film is formed on a substrate to be processed using the organic film-forming material of the present invention, the organic film-forming method of the present invention may be used.

[0218] Then, a resist interlayer film (silicon-containing resist interlayer film) is formed on the organic film using a resist interlayer film material containing silicon atoms. For the silicon-containing resist interlayer film material, a polysiloxane-based interlayer film material is preferred. By making the silicon-containing resist interlayer film have an antireflection effect, reflection can be suppressed. In particular, for 193nm exposure, if a material containing a large number of aromatic groups and having a high etching selectivity with the substrate is used as the organic film forming material, the k value becomes higher and the substrate reflection becomes higher. By making the silicon-containing resist interlayer film have an absorption having an appropriate k value, reflection can be suppressed and the substrate reflection can be made less than 0.5%. As a silicon-containing resist interlayer film with an antireflection effect, it is preferred to use an anthracene in a pendant structure or a polysiloxane structure for 248nm and 157nm exposure, and a polysiloxane having a phenyl group or a light-absorbing group having a silicon-silicon bond in a pendant structure or a polysiloxane structure for 193nm exposure, and cross-linking with acid or heat.

[0219] Then, a resist upper film is formed on the silicon-containing resist intermediate film using a resist upper film material composed of a photoresist composition. As the resist upper film material, either a positive type or a negative type can be used, and the same photoresist composition as commonly used can be used. After spin coating the resist upper film material, it is ideal to pre-bake at 60 to 180°C for 10 to 300 seconds. Thereafter, exposure is performed according to the usual method, and post-exposure baking (PEB) and development are further performed to obtain a resist upper film pattern. In addition, there is no particular restriction on the thickness of the resist upper film, and it is preferably 30 to 500 nm, and particularly preferably 50 to 400 nm.

[0220] Then, a circuit pattern (resist upper film pattern) is formed on the resist upper film. In forming the circuit pattern, it is ideal to form the circuit pattern by photolithography using light with a wavelength of 10 nm to 300 nm, direct drawing using an electron beam, nanoimprinting, or a combination of these.

[0221] In addition, the exposure light is high-energy radiation with a wavelength of less than 300nm, specifically, far ultraviolet light, KrF excimer laser light (248nm), ArF excimer laser light (193nm), F2 laser light (157nm), Kr2 laser light (146nm), Ar2 laser light (126nm), 3 to 20nm soft X-ray (EUV), electron beam (EB), ion beam, X-ray, etc.

[0222] Furthermore, in forming the circuit pattern, it is preferable to develop the circuit pattern by alkali development or an organic solvent.

[0223] Then, the resist upper film with the circuit pattern formed thereon is used as a mask to transfer the pattern to the silicon-containing resist intermediate film by etching. The etching of the silicon-containing resist intermediate film using the resist upper film pattern as a mask is preferably performed using a fluorocarbon-based gas. Thus, the silicon-containing resist intermediate film pattern is formed.

[0224] Then, the pattern is transferred to the organic film by etching using the silicon-containing resist interlayer film with the transferred pattern as a mask. Since the silicon-containing resist interlayer film exhibits higher etching resistance to oxygen or hydrogen than organic matter, it is more preferable to use an etching gas containing oxygen or hydrogen as the main component to etch the organic film using the silicon-containing resist interlayer film pattern as a mask. In this way, an organic film pattern can be formed.

[0225] Then, the pattern is transferred to the processed substrate by etching using the organic film having the transferred pattern as a mask. The etching of the processed substrate (processed layer) can be carried out by a common method. For example, if the processed substrate is SiO2, SiN, or a silicon dioxide-based low-k dielectric film, etching using chlorofluorocarbon-based gas as the main body is performed. If it is p-Si or Al, W, etching using chlorine-based or bromine-based gas as the main body is performed. In the case where the substrate is processed by etching using chlorofluorocarbon-based gas, the silicon-containing resist intermediate film pattern is peeled off while the substrate is processed. On the other hand, in the case where the substrate is processed by etching using chlorine-based or bromine-based gas, in order to peel off the silicon-containing resist intermediate film pattern, it is necessary to perform dry etching peeling using chlorofluorocarbon-based gas after the substrate is processed.

[0226] The organic film obtained by using the organic film-forming material of the present invention can be made to have excellent etching resistance when etching the substrate to be processed as described above.

[0227] [Four-layer resist method using silicon-containing resist interlayer and organic antireflection film]

[0228] In addition, the present invention provides a pattern forming method, which uses the above-mentioned organic film forming material of the present invention to form an organic film on a processed substrate, uses a resist intermediate film material containing silicon atoms to form a silicon-containing resist intermediate film on the organic film, forms an organic anti-reflective film on the silicon-containing resist intermediate film, uses a resist upper film material composed of a photoresist composition to form a resist upper film on the organic anti-reflective film, forms a circuit pattern on the resist upper film, uses the resist upper film forming the circuit pattern as a mask to transfer the pattern to the above-mentioned organic anti-reflective film and the above-mentioned silicon-containing resist intermediate film by dry etching, uses the silicon-containing resist intermediate film with the transferred pattern as a mask to transfer the pattern to the above-mentioned organic film by etching, and further uses the organic film with the transferred pattern as a mask to transfer the pattern to the above-mentioned processed substrate by etching.

[0229] This method can be performed in the same manner as the above-mentioned three-layer resist method using the silicon-containing resist interlayer film, except that an organic antireflection film (BARC) is formed between the silicon-containing resist interlayer film and the resist upper film.

[0230] The organic anti-reflection film can be formed by spin coating using a known organic anti-reflection film material.

[0231] [Three-layer resist method using an inorganic hard mask]

[0232] In addition, the present invention provides a pattern forming method, which is a pattern forming method using a three-layer resist method using the organic film forming material of the present invention, wherein an organic film is formed on a substrate to be processed using the organic film forming material of the present invention, an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film and a titanium nitride film is formed on the organic film, a resist upper film material composed of a photoresist composition is used to form a resist upper film on the inorganic hard mask, a circuit pattern is formed on the resist upper film, the resist upper film on which the circuit pattern is formed is used as a mask to transfer the pattern to the inorganic hard mask by etching, the inorganic hard mask to which the pattern is transferred is used as a mask to transfer the pattern to the organic film by etching, and further the organic film to which the pattern is transferred is used as a mask to transfer the pattern to the substrate to be processed by etching.

[0233] This method can be performed in the same manner as the above-mentioned three-layer resist method using the silicon-containing resist interlayer film, except that an inorganic hard mask is formed on the organic film instead of the silicon-containing resist interlayer film.

[0234] The inorganic hard mask selected from silicon oxide film, silicon nitride film, silicon oxide nitride film (SiON film), titanium oxide film and titanium nitride film can be formed by CVD method, ALD method and the like. The method for forming silicon nitride film is described in Japanese Patent Application Publication No. 2002-334869, International Publication No. 2004 / 066377 and the like. The film thickness of the inorganic hard mask is preferably 5 to 200 nm, more preferably 10 to 100 nm. As for the inorganic hard mask, it is most preferable to use SiON film which has a high effect as an anti-reflection film. The substrate temperature when forming SiON film is 300 to 500°C, so it is necessary for the organic film to withstand a temperature of 300 to 500°C. The organic film formed using the organic film forming composition of the present invention has high heat resistance and can withstand a high temperature of 300 to 500°C, so it is possible to combine the inorganic hard mask formed by CVD method or ALD method with the organic film formed by spin coating method.

[0235] [Four-layer resist method using inorganic hard mask and organic anti-reflective film]

[0236] In addition, the present invention provides a pattern forming method, which is a pattern forming method by a four-layer resist method using the organic film forming material of the present invention, wherein an organic film is formed on a substrate to be processed using the organic film forming material of the present invention, an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film and a titanium nitride film is formed on the organic film, an organic antireflection film is formed on the inorganic hard mask, a resist upper film material composed of a photoresist composition is used to form a resist upper film on the organic antireflection film, a circuit pattern is formed on the resist upper film, the resist upper film on which the circuit pattern is formed is used as a mask to transfer the pattern to the organic antireflection film and the inorganic hard mask by etching, the inorganic hard mask to which the pattern is transferred is used as a mask to transfer the pattern to the organic film by etching, and further the organic film to which the pattern is transferred is used as a mask to transfer the pattern to the substrate to be processed by etching.

[0237] This method can be performed in the same manner as the above-mentioned three-layer resist method using an inorganic hard mask, except that an organic antireflection film (BARC) is formed between the inorganic hard mask and the resist upper layer film.

[0238] In particular, when a SiON film is used as an inorganic hard mask, the two-layer antireflection film of the SiON film and the BARC can suppress reflection even in immersion exposure with a high NA exceeding 1.0. Another advantage of forming a BARC is that it has the effect of reducing the tailing of the resist upper film pattern directly above the SiON film.

[0239] Here, the three-layer resist method of the present invention is an example of a pattern forming method. Figure 2 As shown in (A) to (F) of the 3-layer resist method, Figure 2 As shown in (A), after an organic film 3 is formed on a workpiece layer 2 formed on a substrate 1 using the organic film forming material of the present invention, a silicon-containing resist intermediate film 4 is formed, and a resist upper film 5 is formed thereon. Then, as Figure 2 As shown in (B), the exposed portion 6 of the resist upper film 5 is exposed and PEB (post-exposure baking) is performed. Figure 2 As shown in (C), development is performed to form a resist upper film pattern 5a. Then, as Figure 2 As shown in (D), the resist upper film pattern 5a is used as a mask, and the silicon-containing resist intermediate film 4 is dry-etched using a chlorofluorocarbon gas to form a silicon-containing resist intermediate film pattern 4a. Then, as shown in Figure 2 As shown in (E), after removing the resist upper film pattern 5a, the silicon-containing resist intermediate film pattern 4a is used as a mask to perform oxygen plasma etching on the organic film 3 to form an organic film pattern 3a. Figure 2As shown in (F), after removing the silicon-containing resist intermediate film pattern 4a, the processed layer 2 is etched using the organic film pattern 3a as a mask to form a pattern 2a.

[0240] When an inorganic hard mask is formed, the silicon-containing resist intermediate film 4 may be replaced with an inorganic hard mask, and when a BARC is formed, a BARC may be formed between the silicon-containing resist intermediate film 4 and the resist upper film 5. The etching of the BARC may be performed continuously before the etching of the silicon-containing resist intermediate film 4, or the etching of the silicon-containing resist intermediate film 4 may be performed by changing the etching device after only the etching of the BARC.

[0241] As described above, according to the pattern forming method of the present invention, a fine pattern can be formed on a substrate to be processed with high precision by a multilayer resist method.

[0242] [Example]

[0243] Hereinafter, the present invention will be described in more detail by showing synthesis examples, embodiments, and comparative examples, but the present invention is not limited thereto. In addition, as for molecular weight and dispersity, the weight average molecular weight (Mw) and number average molecular weight (Mn) calculated as polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent are obtained, and the dispersity (Mw / Mn) is obtained.

[0244] Synthesis Example Synthesis of Compounds for Organic Film-Forming Materials

[0245] The following tetrahydric alcohols or hexahydric alcohols (B1) to (B4) and fluorobenzenes (C1) to (C3) were used in the synthesis of the compounds (A1) to (A7) for organic film forming materials. In addition, the comparative example synthetic raw materials (D1) to (D7) were used in the comparative example compounds (R1) to (R5).

[0246] Tetrahydric or hexahydric alcohol:

[0247] [Chemistry 31]

[0248]

[0249] Fluorobenzene:

[0250] [Chemistry 32]

[0251]

[0252] Comparative synthesis examples using synthetic raw materials:

[0253] [Chemistry 33]

[0254]

[0255] [Synthesis Example 1] Synthesis of Compound (A1)

[0256] To 20.0 g of tetraol (B1), 24.7 g of fluorobenzene (C1), and 36.0 g of potassium carbonate, 200 g of N-methylpyrrolidone was added, and the reaction was carried out for 24 hours at an internal temperature of 160°C under a nitrogen environment. After cooling to room temperature, 300 ml of methyl isobutyl ketone and 300 ml of pure water were added to the reaction solution to make it uniform, and the separated water layer was removed. The organic layer was washed twice with 100 ml of 3% nitric acid aqueous solution and 5 times with 100 ml of pure water, and then the organic layer was dried under reduced pressure. After adding 100 g of THF to the residue to make a uniform solution, crystallization was carried out with 300 g of hexane. The precipitated crystals were separated by filtration, washed twice with 200 g of hexane and recovered. The recovered crystals were vacuum dried at 70°C to obtain the mixture represented by (A1) below. The isomer ratio measured by LC is also shown. The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) determined by GPC were as follows.

[0257] (A1): Mw=640, Mw / Mn=1.03

[0258] [Chemistry 34]

[0259]

[0260] [Synthesis Example 2] Synthesis of Compound (A2)

[0261] To 20.0 g of tetraol (B1), 20.3 g of fluorobenzene (C2), and 36.0 g of potassium carbonate, 200 g of N-methylpyrrolidone was added, and the reaction was carried out at an internal temperature of 140°C for 24 hours under a nitrogen environment. After cooling to room temperature, 300 ml of methyl isobutyl ketone and 300 ml of pure water were added to the reaction solution to make it uniform, and the separated water layer was removed. The organic layer was washed twice with 100 ml of 3% nitric acid aqueous solution and 5 times with 100 ml of pure water, and then the organic layer was dried under reduced pressure. After adding 100 g of THF to the residue to make a uniform solution, crystallization was carried out with 300 g of hexane. The precipitated crystals were separated by filtration, washed twice with 200 g of hexane and recovered. The recovered crystals were vacuum dried at 70°C to obtain the mixture represented by (A2) below. The isomer ratio measured by LC is also shown. The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) determined by GPC were as follows.

[0262] (A2): Mw=570, Mw / Mn=1.05

[0263] [Chemistry 35]

[0264]

[0265] [Synthesis Example 3] Synthesis of Compound (A3)

[0266] To 20.0 g of tetraol (B2), 22.3 g of fluorobenzene (C1), and 32.1 g of potassium carbonate, 200 g of N-methylpyrrolidone was added, and the reaction was carried out for 24 hours under a nitrogen environment at an internal temperature of 160°C. After cooling to room temperature, 300 ml of methyl isobutyl ketone and 300 ml of pure water were added to the reaction solution to make it uniform, and the separated water layer was removed. The organic layer was washed twice with 100 ml of 3% nitric acid aqueous solution and 5 times with 100 ml of pure water, and then the organic layer was dried under reduced pressure. After adding 100 g of THF to the residue to make a uniform solution, crystallization was carried out with 300 g of hexane. The precipitated crystals were separated by filtration, washed twice with 200 g of hexane and recovered. The recovered crystals were vacuum dried at 70°C to obtain the mixture represented by (A3) below. The isomer ratio measured by LC is also shown. The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) determined by GPC were as follows.

[0267] (A3): Mw=670, Mw / Mn=1.02

[0268] [Chemistry 36]

[0269]

[0270] [Synthesis Example 4] Synthesis of Compound (A4)

[0271] To 20.0 g of tetraol (B2), 18.1 g of fluorobenzene (C2), and 32.1 g of potassium carbonate, 200 g of N-methylpyrrolidone was added, and the reaction was carried out for 24 hours at an internal temperature of 140°C under a nitrogen environment. After cooling to room temperature, 300 ml of methyl isobutyl ketone and 300 ml of pure water were added to the reaction solution to make it uniform, and the separated water layer was removed. The organic layer was washed twice with 100 ml of 3% nitric acid aqueous solution and five times with 100 ml of pure water, and then the organic layer was dried under reduced pressure. After adding 100 g of THF to the residue to make a uniform solution, crystallization was carried out with 300 g of hexane. The precipitated crystals were separated by filtration, washed twice with 200 g of hexane and recovered. The recovered crystals were vacuum dried at 70°C to obtain the mixture represented by (A4) below. The isomer ratio measured by LC is also shown. The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) determined by GPC were as follows.

[0272] (A4): Mw=610, Mw / Mn=1.04

[0273] [Chemistry 37]

[0274]

[0275] [Synthesis Example 5] Synthesis of Compound (A5)

[0276] To 20.0 g of tetraol (B3), 18.1 g of fluorobenzene (C2), and 25.4 g of potassium carbonate, 200 g of N-methylpyrrolidone was added, and the reaction was carried out for 24 hours at an internal temperature of 140°C under a nitrogen environment. After cooling to room temperature, 300 ml of methyl isobutyl ketone and 300 ml of pure water were added to the reaction solution to make it uniform, and the separated water layer was removed. The organic layer was washed twice with 100 ml of 3% nitric acid aqueous solution and five times with 100 ml of pure water, and then the organic layer was dried under reduced pressure. After adding 100 g of THF to the residue to make a uniform solution, crystallization was carried out with 300 g of hexane. The precipitated crystals were separated by filtration, washed twice with 200 g of hexane and recovered. The recovered crystals were vacuum dried at 70°C to obtain the mixture represented by (A5) below. The isomer ratio measured by LC is also shown. The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) determined by GPC were as follows.

[0277] (A5): Mw=720, Mw / Mn=1.05

[0278] [Chemistry 38]

[0279]

[0280] [Synthesis Example 6] Synthesis of Compound (A6)

[0281] To 20.0 g of tetraol (B3), 16.2 g of fluorobenzene (C3), and 25.4 g of potassium carbonate, 200 g of N-methylpyrrolidone was added, and the reaction was carried out for 8 hours at an internal temperature of 120°C under a nitrogen environment. After cooling to room temperature, 300 ml of methyl isobutyl ketone and 300 ml of pure water were added to the reaction solution to make it uniform, and the separated water layer was removed. The organic layer was washed twice with 100 ml of 3% nitric acid aqueous solution and 5 times with 100 ml of pure water, and then the organic layer was dried under reduced pressure. After adding 100 g of THF to the residue to make a uniform solution, crystallization was carried out with 400 g of methanol. The precipitated crystals were separated by filtration, washed twice with 300 g of methanol and recovered. The recovered crystals were vacuum dried at 70°C to obtain the mixture represented by (A6) below. The isomer ratio measured by LC is also shown. The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) determined by GPC were as follows.

[0282] (A6): Mw=760, Mw / Mn=1.04

[0283] [Chemistry 39]

[0284]

[0285] [Synthesis Example 7] Synthesis of Compound (A7)

[0286] To 20.0 g of hexavalent alcohol (B4), 25.9 g of fluorobenzene (C2), and 45.4 g of potassium carbonate, 250 g of N-methylpyrrolidone was added, and the reaction was carried out for 24 hours at an internal temperature of 140°C under a nitrogen environment. After cooling to room temperature, 400 ml of methyl isobutyl ketone and 400 ml of pure water were added to the reaction solution to make it uniform, and the separated water layer was removed. The organic layer was washed twice with 100 ml of 3% nitric acid aqueous solution and 5 times with 100 ml of pure water, and then the organic layer was dried under reduced pressure. After adding 100 g of THF to the residue to make a uniform solution, crystallization was carried out with 350 g of methanol. The precipitated crystals were separated by filtration, washed twice with 200 g of methanol and recovered. The recovered crystals were vacuum dried at 70°C to obtain the mixture represented by (A7) below. The isomer ratio measured by LC is also shown. The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) determined by GPC were as follows.

[0287] (A7): Mw=790, Mw / Mn=1.08

[0288] [Chemistry 40]

[0289]

[0290] [Synthesis Example 8] Synthesis of Compound (R1) for Comparative Example

[0291] [Chemistry 41]

[0292]

[0293] For the comparative example, 20.0 g of synthetic raw material (D1), 16.4 g of synthetic raw material (D2) and 23.3 g of potassium carbonate were added with 200 g of N-methylpyrrolidone, and the reaction was carried out for 24 hours at an internal temperature of 140°C under a nitrogen environment. After cooling to room temperature, 300 ml of methyl isobutyl ketone and 300 ml of pure water were added to the reaction solution to make it uniform, and the separated water layer was removed. The organic layer was washed twice with 100 ml of 3% nitric acid aqueous solution and 5 times with 100 ml of pure water, and then the organic layer was dried under reduced pressure. After adding 100 g of THF to the residue to make a uniform solution, crystallization was carried out with 350 g of methanol. The precipitated crystals were separated by filtration, washed twice with 200 g of methanol and recovered. (R1) was obtained by vacuum drying the recovered crystals at 70°C. The weight average molecular weight (Mw) and dispersity (Mw / Mn) obtained by GPC are the following results.

[0294] (R1): Mw=580, Mw / Mn=1.03

[0295] [Synthesis Example 9] Synthesis of Compound (R2) for Comparative Example

[0296] [Chemistry 42]

[0297]

[0298] 20 g of the synthetic raw material (D3) for comparative example, 8.4 g of trimethylsilyl acetylene, 1.0 g of dichlorobistriphenylphosphine palladium (II), 0.4 g of copper (I) iodide, 20 g of triethylamine, and 150 g of THF were added, and the reaction was carried out for 8 hours at an internal temperature of 70°C under a nitrogen atmosphere. After cooling to room temperature, the insoluble components were separated by filtration, and 300 g of methanol was added to crystallize. The obtained crystals were dissolved in 300 ml of ethyl acetate, and washed 5 times with 100 ml of 3% hydrochloric acid aqueous solution, 100 ml of 3% sodium bicarbonate aqueous solution, and 100 ml of pure water in sequence, and then the organic layer was dried under reduced pressure. To the solid obtained by reduced pressure drying, 16.0 g of potassium carbonate, 80 g of THF, and 30 g of methanol were added, and the reaction was carried out at room temperature for 4 hours. After cooling to room temperature, the organic layer was washed twice with 100 ml of 3% nitric acid aqueous solution, and washed 5 times with 100 ml of pure water, and then the organic layer was dried under reduced pressure. After adding 60 g of THF to the residue to make a uniform solution, 200 g of methanol was used to crystallize it. The precipitated crystals were separated by filtration, washed twice with 100 g of methanol and recovered. The recovered crystals were vacuum dried at 70°C to obtain (R2). The weight average molecular weight (Mw) and dispersity (Mw / Mn) obtained by GPC were the following results.

[0299] (R2): Mw=660, Mw / Mn=1.01

[0300] [Synthesis Example 10] Synthesis of Compound (R3) for Comparative Example

[0301] [Chemistry 43]

[0302]

[0303] For the comparative example, 10.0 g of synthetic raw material (D4), 39.3 g of synthetic raw material (D5) and 24.0 g of potassium carbonate were added with 200 g of N-methylpyrrolidone, and the reaction was carried out for 24 hours at an internal temperature of 140°C under a nitrogen environment. After cooling to room temperature, 400 ml of methyl isobutyl ketone and 300 ml of pure water were added to the reaction solution to make it uniform, and the separated water layer was removed. The organic layer was washed twice with 100 ml of 3% nitric acid aqueous solution and 5 times with 100 ml of pure water, and then the organic layer was dried under reduced pressure. After adding 100 g of THF to the residue to make a uniform solution, crystallization was carried out with 400 g of methanol. The precipitated crystals were separated by filtration, washed twice with 300 g of methanol and recovered. (R3) was obtained by vacuum drying the recovered crystals at 70°C. The weight average molecular weight (Mw) and dispersity (Mw / Mn) obtained by GPC are as follows.

[0304] (R3): Mw=1520, Mw / Mn=1.06

[0305] [Synthesis Example 11] Synthesis of Compound (R4) for Comparative Example

[0306] [Chemistry 44]

[0307]

[0308] For the comparative example, 30.0 g of synthetic raw material (D6), 0.03 g of copper (I) iodide, and 0.20 g of tetramethylethylenediamine were added to 120 g of toluene, and air was introduced from the air bubbler to bubble, and the reaction was carried out at an internal temperature of 50 ° C for 3 hours. After cooling to room temperature, a mixed solution of 20 g of concentrated hydrochloric acid and 500 g of methanol was added to precipitate crystals. The precipitated crystals were filtered and separated, and washed 5 times with 200 g of methanol and recovered. (R4) was obtained by vacuum drying the recovered crystals at 70 ° C. The weight average molecular weight (Mw) and dispersity (Mw / Mn) obtained by GPC are the following results.

[0309] (R4): Mw=3100, Mw / Mn=1.85

[0310] [Synthesis Example 12] Synthesis of Compound (R5) for Comparative Example

[0311] [Chemistry 45]

[0312]

[0313] Under a nitrogen environment, 80 g of the comparative example synthetic raw material (D7), 22 g of a 37% formalin solution, and 250 g of 1,2-dichloroethane were prepared into a uniform solution at a liquid temperature of 70 ° C, and then 5 g of methanesulfonic acid was slowly added, and the reaction was carried out at a liquid temperature of 80 ° C for 12 hours. After cooling to room temperature, 500 ml of MIBK was added, and the organic layer was washed 5 times with 200 g of pure water, and then the organic layer was dried under reduced pressure. After adding 300 g of THF to the residue to prepare a uniform solution, the polymer was precipitated again with 2000 g of hexane. The precipitated polymer was separated by filtration and dried under reduced pressure to obtain a compound (R5). The weight average molecular weight (Mw) and dispersity (Mw / Mn) obtained by GPC are the following results.

[0314] (R5): Mw=3000, Mw / Mn=1.58

[0315] The structural formula, weight average molecular weight (Mw) and dispersity (Mw / Mn) of the compounds (A1) to (A7) obtained above are shown in Tables 1 and 2. In addition, the compounds (R1) to (R5) used in the comparative examples are also shown in Table 3.

[0316] [Table 1]

[0317]

[0318] [Table 2]

[0319]

[0320] [Table 3]

[0321]

[0322] Preparation of organic film-forming materials (UDL-1 to 9, comparative UDL-1 to 5)

[0323] The above compounds (A1) to (A7) and (R1) to (R5), as well as (S1) 1,6-diacetoxyhexane as a high boiling point solvent: boiling point 260°C, and (S2) tripropylene glycol monomethyl ether: boiling point 242°C were dissolved in a solvent containing 0.1% by mass of propylene glycol monomethyl ether acetate (PGMEA) or cyclohexanone (CyHO) and FC-4430 (manufactured by Sumitomo 3M Co., Ltd.) at the ratios shown in Table 4, and filtered with a 0.1 μm fluororesin filter to prepare organic film-forming materials (UDL-1 to 9, comparative UDL-1 to 5), respectively.

[0324] [Table 4]

[0325]

[0326] Example 1 Solvent Resistance Measurement (Examples 1-1 to 1-9, Comparative Examples 1-1 to 1-5)

[0327] The above-modulated organic film forming materials (UDL-1 to 9, comparative UDL-1 to 5) were coated on a silicon substrate, baked at 450°C for 60 seconds under a nitrogen gas flow with an oxygen concentration controlled to be below 0.2%, and the film thickness was measured. PGMEA solvent was dispensed thereon, left for 30 seconds and spin dried, and baked at 100°C for 60 seconds to evaporate PGMEA, and the film thickness was measured to obtain the film thickness difference before and after PGMEA treatment. These results are shown in Table 5.

[0328] [Table 5]

[0329]

[0330]

[0331] As shown in Table 5, it can be seen that the organic film forming material of the present invention (Examples 1-1 to 1-9) has a residual film rate of 99.8% or more after PGMEA treatment, and a cross-linking reaction occurs even in a nitrogen environment to show sufficient solvent resistance. On the other hand, Comparative Examples 1-1, 1-3 to 1-5 with an ether structure have insufficient heat resistance, and the residual film rate after PGMEA treatment is less than 99.5%. Among them, the residual film rate of Comparative Examples 1-3 and 1-5 is less than 90%. Comparative Example 1-2, which does not have an ether structure, exhibits solvent resistance and a residual film rate of more than 99.8%. From these results, it can be seen that the dioxin ring system is different from the ether structure. Although it contains heteroatoms, it forms a heterocyclic structure, so it has excellent heat resistance.

[0332] Example 2 Evaluation of heat resistance properties (Examples 2-1 to 2-9, Comparative Examples 2-1 to 2-5)

[0333] The above-mentioned organic film-forming materials (UDL-1 to 9, comparative UDL-1 to 5) were coated on a silicon substrate, respectively, and calcined at 180°C in air to form a 200 nm coating film, and the film thickness was measured. The substrate was further baked at 450°C for 10 minutes under a nitrogen gas flow with an oxygen concentration controlled to be less than 0.2%, and the film thickness was measured. These results are shown in Table 6.

[0334] [Table 6]

[0335]

[0336]

[0337] As shown in Table 6, the organic film forming material of the present invention (Examples 2-1 to 2-9) did not decrease in film thickness by 3% even after calcination at 450°C for 10 minutes. The organic film forming material of the present invention can form an organic film having high heat resistance even under such a high temperature condition of 450°C. In particular, in Examples 2-2, 2-4, 2-5, 2-6, 2-7, 2-8, and 2-9 in which R1 has an ethynyl group, it can be seen that the film thickness decrease is suppressed to less than 1% even after baking at 450°C for 10 minutes, and the heat resistance is particularly excellent. On the other hand, in Comparative Examples 2-1, 2-3, 2-4, and 2-5 having an ether bond, a large film thickness decrease of more than 40% occurs. As with the result of Example 1, it can be seen that the dioxin ring has high heat resistance even when it contains a heteroatom.

[0338] Example 3 Evaluation of landfill characteristics (Examples 3-1 to 3-9, Comparative Examples 3-1 to 3-5)

[0339] like Figure 3 As shown in FIG. 1 , the organic film forming materials (UDL-1 to 9, comparative UDL-1 to 5) were coated on a SiO2 wafer substrate having a dense hole pattern (hole diameter 0.16 μm, hole depth 0.50 μm, distance between the centers of two adjacent holes 0.32 μm), and baked at 450° C. for 600 seconds using a hot plate in a nitrogen gas flow with an oxygen concentration controlled to be less than 0.2%, to form an organic film 8. The substrate used was as follows Figure 3 The base substrate 7 (SiO2 wafer substrate) with a dense hole pattern shown in (G) (top view) and (H) (cross-sectional view). The cross-sectional shape of each wafer substrate obtained was observed using a scanning electron microscope (SEM) to confirm whether there were no voids inside the holes and that the holes were filled with an organic film 8. The results are shown in Table 7. When an organic film material with poor filling characteristics was used, voids were generated inside the holes in this evaluation. When an organic film material with good filling characteristics was used, as shown in this evaluation, Figure 3 As shown in (I), there is no space inside the hole and the organic film 8 is filled.

[0340] [Table 7]

[0341]

[0342] As shown in Table 7, it can be confirmed that the organic film forming material of the present invention (Examples 3-1 to 3-9) can fill the hole pattern without generating voids and has good filling characteristics. On the other hand, in Comparative Examples 3-1, 3-3, 3-4, and 3-5, voids are generated due to insufficient heat resistance as in Example 2. Based on this result, it can be confirmed that the organic film forming material of the present invention has good filling characteristics.

[0343] Example 4 Evaluation of planarization characteristics (Examples 4-1 to 4-9, Comparative Examples 4-1 to 4-5)

[0344] The organic film forming materials (UDL-1 to 9, comparative UDL-1 to 5) were applied to the surfaces having the giant isolated groove pattern ( Figure 4 On a base substrate 9 (SiO2 wafer substrate) with (J), groove width 10μm, and groove depth 0.10μm), after baking at 450°C for 60 seconds under a nitrogen gas flow with an oxygen concentration controlled below 0.2% to form an organic film 10, an NX10 atomic force microscope (AFM) manufactured by Park Systems Corp. was used to observe the height difference delta10 of the organic film between the groove part and the non-groove part. The results are shown in Table 8. In this evaluation, the smaller the height difference, the better the planarization characteristics. In addition, in this evaluation, the groove pattern with a depth of 0.10μm is planarized using an organic film material with a normal film thickness of about 0.2μm to evaluate the quality of the planarization characteristics, so it is a strict evaluation condition.

[0345] [Table 8]

[0346]

[0347] As shown in Table 8, it can be confirmed that the organic film forming material of the present invention (Examples 4-1 to 4-9) has a small height difference between the groove part and the non-groove part of the organic film compared to Comparative Examples 4-1 to 4-5, and has excellent flattening properties. In Comparative Examples 4-1, 4-3, and 4-4, although the fluidity is imparted by the ether bond and relatively good flatness is exhibited, as shown in the results of the heat resistance evaluation of Example 2, the heat resistance is insufficient, so baking at 450°C will cause the film to shrink significantly, resulting in poor flatness. In addition, in Comparative Example 4-2, acetylene groups are used as cross-linking groups, and the heat resistance is excellent, but because there is no dioxin ring structure like the present invention, the fluidity cannot be improved, resulting in poor flatness. In addition, if Examples 4-8 and 4-9 to which a high boiling point solvent is added are compared with Examples 4-2 and 4-5 to which a high boiling point solvent is not added, it can be seen that the flatness is further improved by adding a high boiling point solvent. From this result. It is found that the material for forming an organic film of the present invention has excellent heat resistance, so that film shrinkage during high-temperature baking is suppressed, and excellent planarization characteristics are exhibited.

[0348] Example 5 Pattern Formation Test (Examples 5-1 to 5-9, Comparative Example 5-1)

[0349] The above-mentioned organic film forming materials (UDL-1 to 9, comparative UDL-2) were coated on a silicon wafer substrate with a 300nm SiO2 film formed thereon, and baked at 450°C for 60 seconds in a nitrogen gas flow with an oxygen concentration controlled to be less than 0.2% to form an organic film (resist lower layer film). A CVD-SiON hard mask was formed thereon, and an organic anti-reflection film material (ARC-29A: manufactured by Nissan Chemical Co., Ltd.) was further coated thereon and baked at 210°C for 60 seconds to form an organic anti-reflection film with a film thickness of 80nm. A single-layer resist for ArF, which was a resist upper layer film material, was coated thereon and baked at 105°C for 60 seconds to form a photoresist film with a film thickness of 100nm. A wet protection film material (TC-1) was coated on the photoresist film and baked at 90°C for 60 seconds to form a protection film with a film thickness of 50nm. In addition, for the comparative UDL-1 and UDL-3 to UDL-5, the heat resistance was poor as in Example 2, so that a CVD-SiON hard mask could not be formed and the subsequent patterning test could not be performed.

[0350] The polymer (RP1), acid generator (PAG1) and basic compound (Amine1) are dissolved in a solvent containing 0.1 mass% of FC-430 (manufactured by Sumitomo 3M Co., Ltd.) according to the proportions in Table 9, and filtered with a 0.1 μm fluororesin filter to prepare an anti-etching upper film material (single-layer anti-etching agent for ArF).

[0351] [Table 9]

[0352]

[0353] The polymer (RP1), acid generator (PAG1), and basic compound (Amine1) used are shown below.

[0354] [Chemistry 46]

[0355]

[0356] The wet protective film material (TC-1) was prepared by dissolving the protective film polymer (PP1) in an organic solvent at the ratio shown in Table 10 and filtering the solution through a 0.1 μm fluororesin filter.

[0357] [Table 10]

[0358]

[0359] The polymer (PP1) used is shown below.

[0360] [Chemistry 47]

[0361]

[0362] Then, the film was exposed using an ArF immersion exposure device (manufactured by Nikon Corporation; NSR-S610C, NA1.30, σ0.98 / 0.65, 35-degree dipole s-polarized illumination, 6% half-step phase shift mask), baked (PEB) at 100°C for 60 seconds, and developed with a 2.38% by mass tetramethylammonium hydroxide (TMAH) aqueous solution for 30 seconds to obtain a 55nm1:1 positive line and space pattern.

[0363] Then, using a Tokyo Electron etching apparatus Telius, the organic anti-reflective film and the CVD-SiON hard mask were etched by dry etching using the resist pattern as a mask to form a hard mask pattern, the organic film was etched using the obtained hard mask pattern as a mask to form an organic film pattern, and the SiO2 film was etched using the obtained organic film pattern as a mask. The etching conditions are as follows.

[0364] Conditions for transferring the resist pattern to the SiON hard mask.

[0365] Chamber pressure 10.0Pa

[0366] RF power 1,500W

[0367] CF4 gas flow rate 75sccm

[0368] O2 gas flow rate 15sccm

[0369] Time 15 sec

[0370] Conditions for transferring the hard mask pattern to the organic film.

[0371] Chamber pressure 2.0Pa

[0372] RF power 500W

[0373] Ar gas flow rate: 75 sccm

[0374] O2 gas flow rate 45sccm

[0375] Time: 120 seconds

[0376] Conditions for transferring organic film patterns to SiO2 films.

[0377] Chamber pressure 2.0Pa

[0378] RF power 2,200W

[0379] C5F 12 Gas flow rate 20sccm

[0380] C2F6 gas flow rate 10sccm

[0381] Ar gas flow rate 300 sccm

[0382] O2 gas flow rate 60sccm

[0383] Time 90 sec

[0384] Table 11 shows the results of observing the pattern cross section using an electron microscope (S-4700) manufactured by Hitachi, Ltd.

[0385] [Table 11]

[0386]

[0387]

[0388] As shown in Table 11, the results of the organic film-forming material of the present invention (Examples 5-1 to 5-9) showed that the resist upper film pattern was finally well transferred to the substrate in any case, confirming that the organic film-forming material of the present invention is suitable for micro-processing by the multilayer resist method. In Comparative Example 5-1, a CVD-SiON hard mask film was formed on the lower film (organic film), but the film had insufficient adhesion, so it peeled off from the substrate during pattern formation and could not form a pattern.

[0389] Example 6 Adhesion Test (Examples 6-1 to 6-9, Comparative Example 6-1)

[0390] The above-mentioned organic film forming materials (UDL-1 to 9, comparison UDL-2) are coated on a SiO2 wafer substrate, and an organic film with a thickness of 200nm is formed by baking at 450°C for 60 seconds under a nitrogen gas flow with an oxygen concentration controlled below 0.2%. The wafer with the organic film is cut into 1×1cm squares, and the cut wafer is mounted on an aluminum needle with epoxy adhesive using a special fixture. After that, the aluminum needle is bonded to the substrate by heating at 150°C for 1 hour in an oven. After cooling to room temperature, the initial adhesion is evaluated based on the resistance using a thin film adhesion strength measuring device (Sebastian Five-A).

[0391] At Figure 5 This figure shows an explanatory diagram showing a method for measuring adhesion. Figure 5 11 is a silicon wafer (substrate), 12 is an organic film, 13 is an aluminum needle with an adhesive, 14 is a support table, 15 is a gripping portion, and 16 indicates a stretching direction. The adhesion force is the average value of the 12-point measurement, and the higher the value, the higher the adhesion to the substrate of the organic film. The adhesion is evaluated by comparing the obtained values. The results are shown in Table 12.

[0392] [Table 12]

[0393]

[0394]

[0395] As shown in Table 12, it can be seen that the organic film-forming materials (Examples 6-1 to 6-9) containing the organic film-forming compound having a dioxin ring of the present invention have excellent adhesion compared to Comparative Example 6-1, which could not form a pattern according to the pattern formation test results of Example 5. The results of the adhesion test also confirmed that the organic film-forming material of the present invention can be suitably used as a pattern forming material.

[0396] It is clear from the above facts that the organic film forming material of the present invention containing the organic film forming compound of the present invention can have both heat resistance of more than 400°C and high filling / planarization characteristics even in an inert gas not containing oxygen, and is therefore extremely useful as an organic film material used in a multilayer resist method. Furthermore, in the pattern forming method of the present invention using the organic film forming material of the present invention, even if the processed substrate is a substrate with a height difference, a fine pattern can be formed with high precision.

[0397] The present invention is not limited to the above-described embodiments. The above-described embodiments are illustrative, and those having substantially the same configuration as the technical concept described in the claims of the present invention and having the same functions and effects are all within the technical scope of the present invention.

[0398] Explanation of symbols

[0399] 1:Substrate

[0400] 2: Processing layer

[0401] 2a: Pattern (pattern formed on the processed layer)

[0402] 3: Organic film

[0403] 3': Organic film forming composition

[0404] 3a: Organic film pattern

[0405] 4: Silicon-containing resist interlayer

[0406] 4a: Silicon-containing resist interlayer pattern

[0407] 5: Resist upper film

[0408] 5a: Resist upper film pattern

[0409] 6: Exposure part

[0410] 7: Base substrate with dense hole pattern

[0411] 8: Organic film

[0412] 9: Base substrate with giant isolated groove pattern

[0413] 10: Organic film

[0414] delta10: height difference between the groove part and the non-groove part of the organic film

[0415] 11: Silicon Wafer

[0416] 12: Organic film

[0417] 13: Aluminum needle with adhesive

[0418] 14: Support Desk

[0419] 15: Grasping Department

[0420] 16: stretching direction

Claims

1. An organic film-forming material, characterized in that: Containing (A) a compound for forming an organic film represented by the following general formula (1A), and (B) an organic solvent; In the formula, W1 is a 4- or 6-valent organic group selected from one of the following formulae: n1 represents an integer of 1 or 2, n2 represents 2 or 3, and R1 each independently represents any one of the following formula (1B); in addition, the hydrogen atom of the benzene ring in the formula may be substituted by a fluorine atom; 2. The organic film-forming material according to claim 1, wherein The component (A) is a compound represented by the following general formula (1C), (1D), or (1E); In the above formula, n1 and R1 are the same as those described above.

3. The organic film-forming material according to claim 1 or 2, wherein The (A) is a compound represented by the following formula (1F), (1G), or (1H); 4. The organic film-forming material according to claim 1 or 2, wherein The ratio Mw / Mn of the weight average molecular weight Mw and the number average molecular weight Mn of the component (A) in terms of polystyrene obtained by gel permeation chromatography is 1.00≤Mw / Mn≤1.

10.

5. The organic film-forming material according to claim 1 or 2, wherein The component (B) is a mixture of one or more organic solvents having a boiling point of less than 180°C and one or more organic solvents having a boiling point of 180°C or higher. 6 . The organic film-forming material according to claim 1 , further comprising at least one of (C) an acid generator, (D) a surfactant, (E) a crosslinking agent, and (F) a plasticizer. 7 . A substrate for manufacturing a semiconductor device, wherein an organic film is formed on the substrate by curing the organic film-forming material according to claim 1 .

8. A method for forming an organic film, which is used in a manufacturing step of a semiconductor device, characterized in that: The organic film forming material according to any one of claims 1 to 6 is spin-coated on a substrate to be processed, and the substrate to be processed coated with the organic film forming material is heat-treated at a temperature of 50° C. to 600° C. for 10 seconds to 7200 seconds in an inert gas environment to obtain a cured film.

9. A method for forming an organic film, which is used in a manufacturing step of a semiconductor device, characterized in that: The organic film-forming material according to any one of claims 1 to 6 is spin-coated on a substrate to be processed, the substrate to be processed on which the organic film-forming material has been coated is heat-treated in air at a temperature of 50°C to 300°C for a period of 5 seconds to 600 seconds to form a coating film, and then heat-treated in an inert gas environment at a temperature of 200°C to 600°C for a period of 10 seconds to 7200 seconds to obtain a cured film.

10. The method for forming an organic film according to claim 8 or 9, wherein: The oxygen concentration in the inert gas is 1% or less.

11. The method for forming an organic film according to claim 8 or 9, wherein: As the substrate to be processed, a substrate to be processed having a structure with a height of 30 nm or more or a height difference is used.

12. A pattern forming method, characterized in that: An organic film is formed on a substrate to be processed using an organic film forming material according to any one of claims 1 to 6, a silicon-containing resist intermediate film is formed on the organic film using a silicon-containing resist intermediate film material, a resist upper film is formed on the silicon-containing resist intermediate film using a photoresist composition, a circuit pattern is formed on the resist upper film, the pattern is transferred to the silicon-containing resist intermediate film by etching using the patterned resist upper film as a mask, the pattern is transferred to the organic film by etching using the silicon-containing resist intermediate film with the transferred pattern as a mask, and the pattern is further transferred to the substrate to be processed by etching using the organic film with the transferred pattern as a mask.

13. A pattern forming method, characterized in that: An organic film is formed on a substrate to be processed using an organic film forming material according to any one of claims 1 to 6, a silicon-containing resist intermediate film is formed on the organic film using a silicon-containing resist intermediate film material, an organic anti-reflective film is formed on the silicon-containing resist intermediate film, a resist upper film is formed on the organic anti-reflective film using a photoresist composition to form a four-layer film structure, a circuit pattern is formed on the resist upper film, the patterned resist upper film is used as a mask to transfer the pattern to the organic anti-reflective film and the silicon-containing resist intermediate film by etching, the pattern transferred by the silicon-containing resist intermediate film is used as a mask to transfer the pattern to the organic film by etching, and the organic film with the transferred pattern is further used as a mask to transfer the pattern to the substrate to be processed by etching.

14. A pattern forming method, characterized in that: An organic film is formed on a substrate to be processed using an organic film forming material according to any one of claims 1 to 6, an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film is formed on the organic film, a resist upper film is formed on the inorganic hard mask using a photoresist composition, a circuit pattern is formed on the resist upper film, the resist upper film with the pattern formed is used as a mask to transfer the pattern to the inorganic hard mask by etching, the inorganic hard mask with the pattern transferred thereto is used as a mask to transfer the pattern to the organic film by etching, and the organic film with the pattern transferred thereto is further used as a mask to transfer the pattern to the substrate to be processed by etching.

15. A pattern forming method, characterized in that: An organic film is formed on a substrate to be processed using the organic film forming material according to any one of claims 1 to 6, an inorganic hard mask selected from a silicon oxide film, a silicon nitride film, a silicon oxide nitride film, a titanium oxide film, and a titanium nitride film is formed on the organic film, an organic antireflection film is formed on the inorganic hard mask, a photoresist composition is used to form a resist upper film on the organic antireflection film to form a four-layer film structure, a circuit pattern is formed on the resist upper film, the resist upper film with the pattern formed is used as a mask to transfer the pattern to the organic antireflection film and the inorganic hard mask by etching, the inorganic hard mask with the pattern transferred thereto is used as a mask to transfer the pattern to the organic film by etching, and the organic film with the pattern transferred thereto is further used as a mask to transfer the pattern to the substrate to be processed by etching.

16. The pattern forming method according to claim 14 or 15, wherein: The inorganic hard mask is formed by a CVD method or an ALD method.

17. The pattern forming method according to any one of claims 12 to 15, wherein: In the formation of this circuit pattern, the circuit pattern is formed by photolithography using light with a wavelength of 10 nm to 300 nm, direct drawing using an electron beam, nanoimprinting, or a combination of these.

18. The pattern forming method according to any one of claims 12 to 15, wherein: In the formation of the circuit pattern, the circuit pattern is developed by alkali development or an organic solvent.

19. The pattern forming method according to any one of claims 12 to 15, wherein: As the processed substrate, a semiconductor device substrate is used, or a semiconductor device substrate on which a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film are formed.

20. The pattern forming method according to claim 19, wherein: As the metal, silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof is used.

21. A compound for forming an organic film, characterized in that: It is represented by the following general formula (1A); In the formula, W1 is a 4- or 6-valent organic group selected from one of the following formulae: n1 represents an integer of 1 or 2, n2 represents 2 or 3, and R1 each independently represents any one of the following formula (1B); in addition, the hydrogen atom of the benzene ring in the formula may be substituted by a fluorine atom; 22. The compound for forming an organic film according to claim 21, wherein The organic film-forming compound is represented by the following general formula (1C), (1D) or (1E); In the above formula, n1 and R1 are the same as described above.

23. The compound for forming an organic film according to claim 21 or 22, wherein The organic film-forming compound is represented by the following formula (1F), (1G) or (1H);

Citation Information

Patent Citations

  • Ethynyl-substituted aromatic compounds, their synthesis, polymers and uses

    JP1999512430A

  • Method and device for forming silicon nitride film, and method for preprocessing of cleaning thereof

    JP2002334869A

  • Organic insulating film-forming composition

    JP2005041938A

  • Material for forming photoresist lower layer film and method for forming pattern

    JP2005128509A

  • Resist lower layer film material and pattern forming method

    JP2006285095A